Frozen Food Consumer’s Purchase Intentions and Decisions Through E-Commerce in The Greater Jakarta Ragion - Maryanti Sitohang; Suprehatin; Andriyono Kilat Adhi (Jurnal Manajemen & Agribisnis, 2021)
The rise of e-commerce provides consumers more opportunities to purchase agricultural and food products including frozen food. This study aims is to examine the effects of different factors on consumers’ intention and decision on purchasing frozen food through e-commerce based on theory of planned behavior (TPB) and technology acceptance model (TAM). This study used the primary data from online survey of 200 respondents in Greater Jakarta who purchased frozen food through e-commerce. Data were analyzed using partial least squares-structural equation modelling (PLS-SEM). The results showed that perceived usefulness and perceived ease of use e-commerce have a positive influence on attitudes. Then attitudes, subjective norms, and behavior control had a significant positive effect on purchase intention. The results also confirmed that consumers’ purchasing decisions on frozen food affecting by their purchase intention. Keywords: : e-commerce, frozen food, purchase intention, TAM, TPB